The Influence of Leadership, Motivation and Incentives on Employee Performance PT. Karya Teknik Utama - Maizar, Maizar; Persada, Indra Nara; Nabella, Septa Diana (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the effect of leadership, motivation, and intensive on employee performance at pt karya teknik utama. The sampling technique in this study is a census, the entire population makes a sample of 72 people. Research instruments interviews and questionnaires. Data analysis using multiple regression tests, t tests, and f tests with spss version 23. The research results are as follows: Leadership has a significant effect on the performance of employees of pt karya teknik utama with a t-count value for the leadership variable of 9.745 greater than the t-table of 1.662 and a significance value of 0.000 less than 0.05. Motivation has an effect and is significant on the performance of employees of pt karya teknik utama with a t-count value for the motivation variable of 3.353 greater than the t-table 1.662 and a significance value of 0.012 less than 0.05. Incentives have no effect and are insignificant to the performance of employees of pt karya teknik utama with a t-count value for incentives of 1.295 smaller than the t-table 1.662 and a significance value of 0.136 greater than 0.05. Leadership, motivation and incentives together have a significant effect on the performance of employees of pt karya teknik utama with an f-count value of 120,116 greater than the f-table of 2,48 and a significance level of 0.000 less than 0.05.